Case studies of instructional leadership for the Life Sciences in two South African schools - Madonsela, Thobile Perseverance (University of the Free State, 2024)
Globally, learner-achievement was prioritised in the past to enhance school reform efforts. Consequently, this led to Instructional Leadership being viewed as the key strategy for improving the quality of teaching and learning as a long-term trajectory for whole-school school improvement. Although Instructional Leadership is seen as a critical component to effectively enhance teaching and learning in schools, studies in this area of education generally speak to the correlation between management, instruction, and learning; but they do not directly address subject-specific Instructional Leadership - hence, the significance of this study. In acknowledging that scholars in the area of educational leadership have not strongly linked their studies to particular school subjects, it was realised that the existence of instructional problems may be sidelined; hence, subject-specific Instructional Leadership need to be prioritised. Consequently, this study explored the area of Instructional Leadership for the Life Sciences as enacted in South African schools. Findings from this study revealed that Instructional Leadership played a crucial role in sustaining school improvement. In addition, the findings indicated that for subject-specific Instructional Leadership in schools to improve, instructional leaders need to be professionally developed to understand the concept of IL, the subject (Life Sciences), and the practices that promote effective teaching and learning of the subject.
Dissertation (M.Ed. (Education Management))--University of the Free State, 2024
Keywords: Instructional leadership; Life Sciences; South African schools; Education management; School community; Science education; Subject-specific instruction; Whole-school development